Preparing for colorectal surgery: a qualitative study of experiences and preferences of patients in Western Canada - Rebecca Wang; Christopher Yao; Stanley H. Hung; Logan Meyers; Jason M. Sutherland; Ahmer Karimuddin; Kristin L. Campbell; Annalijn I. Conklin (BMC Health Services Research, 2022)
Highlights • Optimising preoperative care for abdominal surgery patients could improve outcomes. • Patient experiences of preparing for colorectal surgery could inform future interventions, but patient-oriented research to improve quality of care is scarce. • There is an unmet need for preoperative support in colorectal surgery. • Future multimodal prehabilitation should incorporate patient preferences.